2004
DOI: 10.1158/0008-5472.can-04-0690
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Block Prostate Cancer in Lady Transgenic Mice

Abstract: The development of chemopreventive agents against prostate cancer would benefit from conclusive evidence of their efficacy in animal models that emulate human disease. To date there has been little in vivo evidence supporting their preventive capabilities. The 12T-10 Lady transgenic model spontaneously develops localized prostatic adenocarcinoma and neuroendocrine cancer followed by metastases, recapitulating the natural history of human prostate cancer in many respects. Using male Lady version of the transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 40 publications
(28 reference statements)
4
81
0
1
Order By: Relevance
“…Interestingly, among selenium-containing reagents, for example, MSA, sodium selenite, Se-Met and Se-(Methyl)selenocysteine, only MSA sensitized prostate cancer cells to TRAIL-mediated apoptosis (Figure 3). Previous studies in prostate and nonprostate cell lines have demonstrated that MSA exerted more powerful inhibitory effect on cell proliferation and viability than Se-Met and Se-(Methyl)selenocysteine (Ip et al, 2000;Dong et al, 2002;Venkateswaran et al, 2002;Zu and Ip, 2003). One potential explanation is that MSA delivers monomethylated selenium species directly to cells (Ip et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among selenium-containing reagents, for example, MSA, sodium selenite, Se-Met and Se-(Methyl)selenocysteine, only MSA sensitized prostate cancer cells to TRAIL-mediated apoptosis (Figure 3). Previous studies in prostate and nonprostate cell lines have demonstrated that MSA exerted more powerful inhibitory effect on cell proliferation and viability than Se-Met and Se-(Methyl)selenocysteine (Ip et al, 2000;Dong et al, 2002;Venkateswaran et al, 2002;Zu and Ip, 2003). One potential explanation is that MSA delivers monomethylated selenium species directly to cells (Ip et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of antioxidants such as lycopene has been associated with reduced prostate cancer risk (76), and scavenging of ROS with antioxidants increases prostate cancer survival in mice (78). However, the role of ROS and lycopene in prostate cancer is not without controversy (37).…”
Section: Cancermentioning
confidence: 99%
“…Although limited by several factors including a small sample size and short duration of therapy, a recent study showed that the SELECT study agents, when given for 3-6 weeks before prostatectomy, created a greater overall difference in gene expression in tumor epithelial cells than administration of vitamin E or selenium alone, including specific increases in p53 gene transcription and translation (98). Using the male Lady version of the TRAMP mice, Venkateswaran et al (99) showed that ad-ministration of antioxidants (vitamin E, selenium and lycopene) in the diet dramatically inhibits PCa development and increases the disease-free survival. A strong correlation between disease-free state and increased levels of the prognostic marker p27(Kip1) and a marked decrease in proliferating cell nuclear antigen expression was also seen by the authors (99).…”
Section: Selenium and Vitamin E Combination: Potential Synergistic Rementioning
confidence: 99%
“…Using the male Lady version of the TRAMP mice, Venkateswaran et al (99) showed that ad-ministration of antioxidants (vitamin E, selenium and lycopene) in the diet dramatically inhibits PCa development and increases the disease-free survival. A strong correlation between disease-free state and increased levels of the prognostic marker p27(Kip1) and a marked decrease in proliferating cell nuclear antigen expression was also seen by the authors (99). However, a subsequent study by the same group suggested that lycopene is an essential component of the combination (100).…”
Section: Selenium and Vitamin E Combination: Potential Synergistic Rementioning
confidence: 99%